The Ambiguous Attitude to Asceticism in Medieval Jewish Philosophy and the Case of Levi ben Avraham - Kreisel, Howard (Jewish Thought, 2021)
In this article, I argue that two major considerations framed medieval Jewish philosophical approaches to asceticism. The first was a legal consideration. The fulfillment of many of the commandments precluded the adoption of an extreme ascetic regimen. The second consideration was a philosophical one. Medieval Jewish philosophical approaches to asceticism are intrinsically linked to approaches to the nature of the soul, its perfection and its final state. In Platonic and Neo-Platonic thought, the goal of life was to free the rational soul from the body and its temptations in a quest for purity and conjunction with the spiritual world. This encouraged a far more ascetic lifestyle in the case of the spiritual elite than the limited constraints upon one's physical appetites imposed by the Torah. Among the earlier medieval Jewish philosophers, whose approach to the soul was basically shaped, albeit indirectly, by Platonic thought with its negative view of the body, the appreciation of more extreme forms of asceticism can be clearly detected. Maimonides, however, is more influenced by Aristotelian thought, with its stress on the perfection of the speculative intellect, which alone survives after death. The implication of this view is that all activities ultimately are to be judged by their contribution to attaining knowledge leading to the intellectual love of God. Hence, even the intellectual elite should engage in ascetic practices only to the point where they further this end. Maimonides' apparently conflicting positions regarding asceticism essentially signal this idea. In general, Maimonides advocates satisfying the demands of the body, but no more than is necessary for its health. Even the Aristotelian "middle way" favored by the Torah, in Maimonides' view, is seen as leaning more in the direction of asceticism. The question for him is in what circumstances should one move even further in that direction, even at the expense of not fulfilling some of the Torah's commandments. The article concludes with a look at the approach of Levi ben Abraham as reflected in his encyclopedia Livyat Ḥen. Levi follows in the footsteps of Maimonides and interprets him along the aforementioned lines. He brings a wealth of material from biblical and rabbinic literature in an attempt to show that there is no conflict in any of the authoritative Jewish sources on this issue. Each of the contradictory rabbinic opinions on this subject deals with a different individual, indicating the regimen required in that one particular case. In general, Levi's encyclopedia comes to complete the Maimonidean project of presenting Judaism as being in harmony with Aristotelian philosophy. Levi's interpretation of Jewish sources on the subject of human perfection and the role asceticism plays in the attainment of this perfection nicely illustrates this point.